MENGANALISIS PROSES BISNIS DALAM MENERAPKAN APLIKASI RESEP DAN BELANJA BAHAN MAKANAN - Purnomo, Yunianto; Putro, Endi; Lee, Francka Sakti; Andry, Johanes Fernandes; Nurprihatin, Filscha; Onggo, Kallista Angelia (ISTEK WIDURI, 2025)
The recipe and grocery shopping application is designed to increase the ease of users in accessing cooking recipes and shopping for groceries in an integrated manner. This research aims to analyze the business processes involved in the application using the Business Process Model and Notation (BPMN) approach. Analysis is carried out to understand the workflow structure, identify potential efficiencies, and produce performance improvements before and after system implementation. The research results show that the application of this application is able to direct processes that were previously manual and fragmented, such as searching for recipes, making shopping lists, and ordering groceries. The BPMN model is used to visualize changes in business process flow, enabling comprehensive evaluation of aspects of time efficiency, error reduction, and increased user satisfaction. This research concludes that the BPMN approach is effective in analyzing and optimizing business processes in recipe and grocery shopping applications. These findings contribute to the development of similar applications, especially in designing systems that are more efficient and responsive to user needs.